2010
DOI: 10.1177/1756283x10361304
|View full text |Cite
|
Sign up to set email alerts
|

Review: Current trends in inflammatory bowel disease: the natural history

Abstract: The description of the prognosis of inflammatory bowel disease (IBD) is based on systematic follow-up of population-based cohorts. A steady increase in incidence of IBD has occurred. The distribution of ulcerative colitis (UC) is fairly uniform with a preponderance of left-sided disease. One-third of Crohn's disease (CD) patients present with colonic disease, one-third with ileocolonic disease and one-third with small bowel disease. IBD is associated with extra-intestinal manifestations (EIMs) in up to 36% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 62 publications
2
53
0
6
Order By: Relevance
“…Leur évolution se fait par poussées entrecoupées de périodes de rémissions plus ou moins longues (28)(29)(30). La diversité des manifestations digestives, la présence de lésions extra-intestinales (oculaires, articulaires, cutanées), le risque inéluctable de complications liées notamment à la fibrose et à la dégénérescence cancéreuse (X18 après 20 ans d'évolution d'une maladie atteignant tout le côlon) en font des maladies difficiles à diagnostiquer et à prendre en charge (31)(32)(33)(34).…”
Section: Miciunclassified
“…Leur évolution se fait par poussées entrecoupées de périodes de rémissions plus ou moins longues (28)(29)(30). La diversité des manifestations digestives, la présence de lésions extra-intestinales (oculaires, articulaires, cutanées), le risque inéluctable de complications liées notamment à la fibrose et à la dégénérescence cancéreuse (X18 après 20 ans d'évolution d'une maladie atteignant tout le côlon) en font des maladies difficiles à diagnostiquer et à prendre en charge (31)(32)(33)(34).…”
Section: Miciunclassified
“…The previous studies have suggested that improvement in mucosal healing rates is associated with better long-term outcomes, improved quality of life, and reduced rates of colectomy [27,28,31]. Using data from ACT1 and ACT2 trials, a subsequent study demonstrated that patients treated with IFX had a significantly lower rate of colectomy and hospitalizations by week 54 than those treated with placebo [32].…”
Section: Discussionmentioning
confidence: 99%
“…Taking the aforementioned information into account, attempts have been made to synthesize copolymers of methacrylic acid and butyl methacrylate in different molar ratios and study the swelling and erosion of the copolymers in simulated gastrointestinal pH condition followed by characterization of the selected copolymers by FTIR, 1 H NMR, PXRD, and DSC. gel permeation chromatography was used to determine the average molecular weights of copolymers.…”
Section: Copolymer Characterizationmentioning
confidence: 99%
“…In CD, there is transmural inflammation of the entire gastrointestinal tract; while in UC, there are ulcers and inflammation, mainly in the mucosa and submucosa of the colon. [1,2] IBD, which are possible risk factor for colon cancer, are increasing rapidly worldwide and account for almost 15% of all deaths. [3][4][5] The incidence of IBD is increasing mainly in the developing countries and its prevalence in Asia and Middle Eastern countries is 4.9-168.3 per 100,000 persons.…”
Section: Introductionmentioning
confidence: 99%